Integrating Punching Training Media into Elementary Education: Enhancing Physical Education Curriculum through Circular Kicks - Martati, Resi Yohana; Bafirman, Bafirman; Alnedral, Alnedral; Okilanda, Ardo; Ockta, Yovhandra (STKIP Singkawang, 2024)
The problem in this study began with the researcher's observation of the weak ability of inner circle kicks of Tarung Derajat athletes at Kurata II Satlat Padang Baru, Padang City. This study aims to determine the Effect of Punching Bag and Punching Pad Training Media and Motivation on Increasing the Strength of Inner Circle Kicks of Tarung Derajat Athletes.This study uses a 2 x 2 factorial research design, where the effect of using punching bag and punching pad training media as independent variables and motivation as the control variable. While the dependent variable is the increase in the strength of inner circle kicks in Tarung Derajat athletes. The sample in this study amounted to 24 people with male and female genders. The sampling method used in this study was the Saturated Sample Technique. Data collection on inner circle kick ability was carried out by performing as many inner circle kicks as possible within 15 seconds with a punching bag as the target. The data on the increase in inner circle kick ability obtained were then analyzed using two-way ANOVA statistics (Two Way ANOVA) 2 x 2. Based on the results of data analysis and interpretation of the results of the study, it shows that: 1 ) there is an effect of increasing the strength of inner circle kicks using punching bag training media. 2) there is an effect of increasing the strength of inner circle kicks using punching pad training media. 3) there is an effect of motivation on increasing the strength of inner circle kicks in combat athletes. 4) The results of the study showed that there was no significant interaction between training media (punching bag and punching pad) with motivation, which means that both factors have their own independent influences.